Head to tail cyclisation of cell-penetrating peptides: impact on GAG-dependent internalisation and direct translocation. Issue 31 (1st April 2019) - Amoura, Mehdi; Illien, Françoise; Joliot, Alain; Guitot, Karine; Offer, John; Sagan, Sandrine; Burlina, Fabienne
Abstract : Small cationic lipidated cyclic cell-penetrating peptides enter efficiently by GAG-dependent endocytosis, expanding the macrocycle favours direct translocation. Abstract : A series of cyclic lipidated oligo-Arg cell penetrating peptides were synthesised with varied macrocycle size and lipid chain anchoring site. The study of their cellular uptake revealed different structural requirements to promote efficient glycosaminoglycan-dependent endocytosis and direct translocation.